Introduction of Red‐Green‐Blue Fluorescent Dyes into a Metal–Organic Framework for Tunable White Light Emission. Issue 37 (7th August 2017) - Wen, Yuehong; Sheng, Tianlu; Zhu, Xiaoquan; Zhuo, Chao; Su, Shaodong; Li, Haoran; Hu, Shengmin; Zhu, Qi‐Long; Wu, Xintao
Abstract : The unique features of the metal–organic frameworks (MOFs), including ultrahigh porosities and surface areas, tunable pores, endow the MOFs with special utilizations as host matrices. In this work, various neutral and ionic guest dye molecules, such as fluorescent brighteners, coumarin derivatives, 4‐(dicyanomethylene)‐2‐methyl‐6‐(p‐dimethylaminostyryl)‐4H‐pyran (DCM), and 4‐(p‐dimethylaminostyryl)‐1‐methylpyridinium (DSM), are encapsulated in a neutral MOF, yielding novel blue‐, green‐, and red‐phosphors, respectively. Furthermore, this study introduces the red‐, green‐, and blue‐emitting dyes into a MOF together for the first time, producing white‐light materials with nearly ideal Commission International ed'Eclairage (CIE) coordinates, high color‐rendering index values (up to 92%) and quantum yields (up to 26%), and moderate correlated color temperature values. The white light is tunable by changing the content or type of the three dye guests, or the excitation wavelength. Significantly, the introduction of blue‐emitting guests in the methodology makes the available MOF host more extensive, and the final white‐light output more tunable and high‐quality. Such strategy can be widely adopted to design and prepare white‐light‐emitting materials. Abstract : Three red‐green‐blue fluorescent dyes are encapsulated simultaneously into a metal–organic framework (MOF) for the first time, producing a series of efficient white‐light‐emitting composites. Significantly, the introduction of the blue‐emitting guest makes the final white light more tunable and higher quality, which can also broaden the available MOF matrices. This strategy will be widely adopted to design and prepare single‐phase white‐light materials.